The rearguard of freedom: the John Birch Society and the development of modern conservatism in the United States, 1958-1968 - Verhoeven, Bart L. (2015)
This thesis aims to investigate the role of the anti-communist John Birch Society within the greater American conservative field. More specifically, it focuses on the period from the Society's inception in 1958 to the beginning of its relative decline in significance, which can be situated after the first election of Richard M. Nixon as president in 1968. The main focus of the thesis lies on challenging more traditional classifications of the JBS as an extremist outcast divorced from the American political mainstream, and argues that through their innovative organizational methods, national presence, and capacity to link up a variety of domestic and international affairs to an overarching conspiratorial narrative, the Birchers were able to tap into a new and powerful force of largely white suburban conservatives and contribute significantly to the growth and development of the post-war New Right. For this purpose, the research interrogates the established scholarship and draws upon key primary source material, including official publications, internal communications and the private correspondence of founder and chairman Robert Welch as well as other prominent members.